Edukasi Literasi Maritim Berbasis Kearifan Lokal dalam Penguatan Ketahanan Sosial dan Penghidupan Berkelanjutan Komunitas Nelayan Bajo: Local Wisdom-Based Maritime Literacy Education in Strengthening Social Resilience and Sustainable Livelihoods among Bajo Fishing Communities - M. Hafiz Sukri; Asna Wirayanti (PT. CASA CENDEKIA MEDIA, 2026)
Maritime local wisdom among the Bajo fishing community in Wawonii Island functions as social capital for maintaining coastal livelihoods, solidarity, and environmental adaptation. However, socio-economic change, resource pressure, and environmental uncertainty require stronger maritime literacy so that local values remain relevant to sustainable livelihood practices. This community service program aimed to improve the Bajo community’s understanding of maritime literacy based on local wisdom in strengthening social resilience and sustainable coastal livelihoods. The program was implemented through preliminary observation, socialization, participatory education, group discussions, and mentoring. The materials covered maritime local wisdom, sustainable utilization of coastal resources, collective work traditions, and socio-economic adaptation strategies for fishing households. The results showed that participants developed better awareness of preserving local values, strengthening cooperation, and managing livelihoods more sustainably. This program implies that local-wisdom-based maritime literacy can be used as an empowerment strategy to reinforce resilience and sustainability among coastal communities.